The Role of Leadership Style, Training and Development, Organizational Culture, and Employee Engagement on Job Satisfaction and Employee Performance - Ishak Ishak; Supriandi Supriandi; Yana Priyana (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study examines the influence of leadership style, training and development, organizational culture, and employee engagement on job satisfaction and employee performance in Indonesian organizations. Using a quantitative approach, data were collected from 250 respondents representing various sectors. A Likert scale (1–5) was employed, and data were analyzed using Structural Equation Modeling – Partial Least Squares (SEM-PLS 3). The results demonstrate that leadership style, training and development, organizational culture, and employee engagement each have a positive and significant impact on job satisfaction. Furthermore, job satisfaction significantly mediates the relationship between these variables and employee performance. Among the predictors, organizational culture and employee engagement exhibit the strongest influence on job satisfaction and performance. The findings highlight the importance of creating an empowering work environment that fosters leadership effectiveness, continuous learning, strong cultural alignment, and high engagement levels. These factors collectively contribute to enhancing employee satisfaction and organizational productivity. The study provides practical insights for human resource managers in Indonesia to design integrated management strategies that improve both employee well-being and overall performance.